2016
DOI: 10.1016/j.jcin.2016.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Valve Type, Size, and Deployment Location Affect Hemodynamics in an In Vitro Valve-in-Valve Model

Abstract: The optimal deployment location for VIV in a 23 PERIMOUNT surgical bioprosthesis was at a +6 mm supra-annular position for a 23-mm SAPIEN valve and at the normal position for both the 23-mm and 26-mm CoreValves. The 26-mm CoreValve had lower gradients, but higher RF and PI than the 23-mm CoreValve and the 23-mm SAPIEN. In their optimal positions, all valves resulted in hemodynamics consistent with the definitions of Valve Academic Research Consortium-2 procedural success. Long-term studies are needed to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 25 publications
4
50
0
Order By: Relevance
“…A higher implantation depth was also associated with reduced pressure gradients and greater EOA in the CoreValve regardless of annular expansion. This finding, which is in agreement with recent valve‐in‐valve studies, suggests that higher valve placement yields fuller leaflet opening and less resistance to flow through the valve (pressure gradients).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A higher implantation depth was also associated with reduced pressure gradients and greater EOA in the CoreValve regardless of annular expansion. This finding, which is in agreement with recent valve‐in‐valve studies, suggests that higher valve placement yields fuller leaflet opening and less resistance to flow through the valve (pressure gradients).…”
Section: Discussionsupporting
confidence: 91%
“…Although THV under‐expansion yields an advantage of reduced thrombosis risk due to less flow stasis, its demerits of increased pressure gradient, and lower EOA may be a cause for concern . This study showed that a 25% underexpanded CoreValve had a 142% higher pressure gradient and 26% lower EOA than a fully expanded one, whereas a 10% underexpanded CoreValve had 36% higher pressure gradient and 10% lower EOA than a fully expanded one.…”
Section: Discussionmentioning
confidence: 68%
“…Other studies have shown that optimal size and placement of TAVs may exist outside the current guidelines 29, 86, 87 . One possible solution to improve post-procedural gradients and minimize PPM is to implant the TAV in a supra-annular position (Figure 6a), effectively bypassing the geometric constraints imposed by the semi-rigid bioprostheses 86, 116, 158 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the larger medium ACn had less leaflet pinwheeling. Pinwheeling is a result of redundant leaflet issue and may have implications for long‐term leaflet function and durability . A high degree of pinwheeling can lead to excessive strain on THV leaflets that may accelerate wear.…”
Section: Discussionmentioning
confidence: 99%